2007
DOI: 10.1289/ehp.10253
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Potential Human-Health Relevance of Volatile Organic Compounds in Drinking Water from Domestic Wells in the United States

Abstract: BackgroundAs the population and demand for safe drinking water from domestic wells increase, it is important to examine water quality and contaminant occurrence. A national assessment in 2006 by the U.S. Geological Survey reported findings for 55 volatile organic compounds (VOCs) based on 2,401 domestic wells sampled during 1985–2002.ObjectivesWe examined the occurrence of individual and multiple VOCs and assessed the potential human-health relevance of VOC concentrations. We also identified hydrogeologic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 17 publications
0
32
0
1
Order By: Relevance
“…Naphthalene is one of polycyclic aromatic hydrocarbons (PAHs), which was commonly detected in China (Guo et al, 2012;Liu and Zhou, 2011;Ma et al, 2014), while seldom detected in the USA (Carter et al, 2008;Moran et al, 2004;Rowe et al, 2007). For many years, naphthalene had been considered as a non-carcinogenic PAH, but in 2000, the US National Toxicology Program revealed clear evidence of the carcinogenic activity of naphthalene in rats (Preuss et al, 2003).…”
Section: Occurrence Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Naphthalene is one of polycyclic aromatic hydrocarbons (PAHs), which was commonly detected in China (Guo et al, 2012;Liu and Zhou, 2011;Ma et al, 2014), while seldom detected in the USA (Carter et al, 2008;Moran et al, 2004;Rowe et al, 2007). For many years, naphthalene had been considered as a non-carcinogenic PAH, but in 2000, the US National Toxicology Program revealed clear evidence of the carcinogenic activity of naphthalene in rats (Preuss et al, 2003).…”
Section: Occurrence Assessmentmentioning
confidence: 99%
“…As the population and demand for safe drinking water increase, it is important to examine water quality and identify contaminants that occur in source water (Rowe et al, 2007), which are thought to be frequently exposed to large amounts of micropollutants originating from the discharge of anthropogenic activities and natural process (Cho et al, 2014). Volatile organic compounds (VOCs), one contaminant group of concern, could be originated from photochemical and microbial activities (Fink, 2007;Watson, 2004) and introduced to the aquatic environment by emission and combustion (Liu and Zhou, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these studies generally have focused on the four most common VOC chemicals (benzene, xylene, toluene, and ethylbenzene), and relatively high concentrations were exposed by researchers in order to evaluate the results. Because analyses of drinking-water (Rowe et al 2007) and urine and venous blood samples have revealed that VOCs commonly occur as complex mixtures and that the concentrations of these substances are often very low (10-100 ppb), the purpose of this research was to investigate the genotoxic effects of very low concentrations of VOCs, currently permissible under drinking-water regulations, total DNA, the antioxidant gene expression, and basepair changes in ribosomal genes.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its high volatility, a major fraction of pDCB used in the aforementioned products is emitted into the air [2][3][4][5]. Furthermore, trace amounts of pDCB have been found in marine and drinking water [6][7][8], food [9], and honey [10][11][12]. pDCB has also been detected in adipose tissues, blood, and maternal milk [13][14][15], indicating widespread human exposure to this compound.…”
Section: Introductionmentioning
confidence: 99%